2017
DOI: 10.1210/js.2017-00102
|View full text |Cite
|
Sign up to set email alerts
|

Treatments to Prevent Bone Loss in Functional Hypothalamic Amenorrhea: A Systematic Review and Meta-Analysis

Abstract: Objective:We conducted a systematic review and meta-analysis of studies that evaluated the effect of hormonal therapy [estrogen therapy including oral contraceptive pills (OCP)] and bisphosphonates in preventing bone loss in patients with functional hypothalamic amenorrhea (FHA).Methods:We searched several electronic databases for controlled and noncontrolled studies that enrolled females of any age presenting with FHA (including athletic, weight loss, and stress-associated amenorrhea/oligomenorrhea) through 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The aim of this intervention is to improve BMD through oestrogen replacement however, more research is required. Oral contraceptives do not restore BMD in athletes and in some cases, are detrimental to BMD [ 115 , 181 , 182 , 183 ]. Irrespective of oestrogen supplementation in the adolescent athlete, potential underlying causes of amenorrhea (energy availability, pituitary issues, ovarian issues, thyroid) should be addressed [ 180 ].…”
Section: Prevention Of Stress Fractures In Adolescent Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this intervention is to improve BMD through oestrogen replacement however, more research is required. Oral contraceptives do not restore BMD in athletes and in some cases, are detrimental to BMD [ 115 , 181 , 182 , 183 ]. Irrespective of oestrogen supplementation in the adolescent athlete, potential underlying causes of amenorrhea (energy availability, pituitary issues, ovarian issues, thyroid) should be addressed [ 180 ].…”
Section: Prevention Of Stress Fractures In Adolescent Athletesmentioning
confidence: 99%
“…Medications typically administered to older persons with osteopenia or osteoporosis (bisphosphonates) are in most cases not appropriate for adolescent athletes, particularly females, due to their potential teratogenic effects and long-half life in bone [ 184 ]. Although case studies have evaluated intravenous bisphosphonates for young adult athletes prone to stress fracture, RCTs investigating the effectiveness and safety of this method of treatment in adolescent athletes or Female Athlete Triad are lacking [ 106 , 181 ]. Bisphosphonates (risedronate) did not prevent stress fracture in Israeli army recruits (mean age 19.1 ± 1.2) [ 185 ].…”
Section: Prevention Of Stress Fractures In Adolescent Athletesmentioning
confidence: 99%
“…The most commonly prescribed treatment for bone loss in premenopausal women with FHA is oral contraceptives (OCPs) or conjugated oestrogens (CE) to improve hypo-oestrogenic environment and, theoretically, protect bone. Systematic reviews have not found OCPs to significantly improve BMD in women with athletic FHA [14][15][16] or anorexia nervosa (AN). 14 17 18 However, some recent randomised controlled trials (RCTs) have reported that transdermal estradiol (TE) is effective in increasing BMD in anorexic and amenorrhoeic premenopausal women.…”
Section: What Are the New Findingsmentioning
confidence: 99%
“…One of the factors that disturb this balance in women is menopause because of physiological and biochemical changes, increased turnover, increased bone resorption [ 7 8 9 ]. The main purpose of treatment is to prevent bone loss and increase bone formation [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%